Porous Inorganic and Hybrid Systems for Drug Delivery: Future Promise in Combatting Drug Resistance and Translation to Botanical Applications - Guo, Junling; Mattos, Bruno D.; Tardy, Blaise L.; Moody, Vanessa M.; Xiao, Gao; Ejima, Hirotaka; Cui, Jiwei; Liang, Kang; Richardson, Joseph J. (Current Medicinal Chemistry, 2019)
Background: Porous micro- and nanoparticles have the capacity to encapsulate a large quantity of therapeutics, making them promising delivery vehicles for a variety of applications. This review aims to highlight the latest development of inorganic and hybrid (inorganic/ organic) particles for drug delivery with an additional emphasis on combatting drug resistant cancer. We go one step further and discuss delivery applications beyond medicinal delivery, as there is generally a translation from medicinal delivery to botanic delivery after a short lag time. Methods: We undertook a search of relevant peer-reviewed publications. The quality of the relevant papers was appraised using standard tools. The characteristics of the papers are described herein, and the relevant material and therapeutic properties are discussed. Results: We discuss 4 classes of porous particles in terms of drug delivery and theranostics. We specifically focus on silica, calcium carbonate, metal-phenolic network, and metalorganic framework particles. Other relevant biomedically relevant applications are discussed and we highlight outstanding therapeutic results in the relevant literature. Conclusion: The findings of this review confirm the importance of studying and utilizing porous particles for therapeutic delivery. Moreover, we show that the properties of porous particles that make them promising for medicinal drug delivery also make them promising candidates for agro-industrial applications.
Keywords: inorganic